Migration and risk of HIV acquisition in Rakai, Uganda: a population-based cohort study. Issue 4 (April 2018) - Olawore, Oluwasolape; Tobian, Aaron A R; Kagaayi, Joseph; Bazaale, Jeremiah M; Nantume, Betty; Kigozi, Grace; Nankinga, Justine; Nalugoda, Fred; Nakigozi, Gertrude; Kigozi, Godfrey; Gray, Ronald H; Wawer, Maria J; et al.
Summary: Background: In sub-Saharan Africa, migrants typically have higher HIV prevalence than non-migrants; however, whether HIV acquisition typically precedes or follows migration is unknown. We aimed to investigate the risk of HIV after migration in Rakai District, Uganda. Methods: In a prospective population-based cohort of HIV-negative participants aged 15–49 years in Rakai, Uganda, between April 6, 1999, and Jan 30, 2015, we assessed the association between migration and HIV acquisition. Individuals were classified as recent in-migrants (≤2 years in community), non-recent in-migrants (>2 years in community), or permanent residents with no migration history. The primary outcome was incident HIV infection. We used Poisson regression to estimate incidence rate ratios (IRRs) of HIV associated with residence status with adjustment for demographics, sexual behaviours, and time. Data were also stratified and analysed within three periods (1999–2004, 2005–11, and 2011–15) in relation to the introduction of combination HIV prevention (CHP; pre-CHP, early CHP, and late CHP). Findings: Among 26 995 HIV-negative people who participated in the Rakai Community Cohort Study survey, 15 187 (56%) contributed one or more follow-up visits (89 292 person-years of follow-up) and were included in our final analysis. 4451 (29%) were ever in-migrants and 10 736 (71%) were permanent residents. 841 incident HIV events occurred, including 243 (29%) among in-migrants. HIV incidence per 100 person-years was significantly increased among recent in-migrants compared with permanent residents, for both women (1·92, 95% CI 1·52–2·43 vs 0·93, 0·84–1·04; IRR adjusted for demographics 1·75, 95% CI 1·33–2·33) and men (1·52, 0·99–2·33 vs 0·84, 0·74–0·94; 1·74, 1·12–2·71), but not among non-recent in-migrants (IRR adjusted for demographics 0·94, 95% CI 0·74–1·19 for women and 1·28, 0·94–1·74 for men). Between the pre-CHP and late-CHP periods, HIV incidence declined among permanent resident men (p<0·0001) and women (p=0·002) and non-recent in-migrant men (p=0·031), but was unchanged among non-recent in-migrant women (p=0·13) and recent in-migrants (men p=0·76; women p=0·84) Interpretation: The first 2 years after migration are associated with increased risk of HIV acquisition. Prevention programmes focused on migrants are needed to reduce HIV incidence in sub-Saharan Africa. Funding: National Institute of Mental Health, the National Institute of Allergy and Infectious Diseases, the National Institute of Child Health and Development, the National Institute for Allergy and Infectious Diseases Division of Intramural Research, National Institutes of Health; the Centers for Disease Control and Prevention; the Bill & Melinda Gates Foundation; and the Johns Hopkins University Center for AIDS Research.